'Faith can come in, but not religion': secularity and its effects on the disaster response to Typhoon Haiyan. Issue 3 (24th October 2017) - Wilkinson, Olivia
Abstract : While other works have analysed what constitutes a faith‐based approach, this study examines what values and practices are employed in a secular approach to disaster response in communities where religion matters. Evidence of a secular approach is assessed in the context of the disaster response to Typhoon Haiyan (2013) in the Philippines, a country in which more than 90 per cent of the population identify themselves as religious. Using interviews with staff members of non‐governmental organisations (NGOs) and focus groups composed of beneficiaries, this paper provides an overview of how respondents commonly characterise a secular approach to disaster response. Results indicate differing NGO and beneficiary opinions on interaction over efficiency and the impartiality and neutrality of organisations. Secularity had a distinct effect on the disaster response to Haiyan, mostly by creating boundaries vis‐à‐vis when and where religion was permitted in the secularised humanitarian system. An awareness of these effects is encouraged to improve interaction with affected populations and local organisations.